2016
DOI: 10.3390/v8090251
|View full text |Cite
|
Sign up to set email alerts
|

Organization, Function, and Therapeutic Targeting of the Morbillivirus RNA-Dependent RNA Polymerase Complex

Abstract: The morbillivirus genus comprises major human and animal pathogens, including the highly contagious measles virus. Morbilliviruses feature single stranded negative sense RNA genomes that are wrapped by a plasma membrane-derived lipid envelope. Genomes are encapsidated by the viral nucleocapsid protein forming ribonucleoprotein complexes, and only the encapsidated RNA is transcribed and replicated by the viral RNA-dependent RNA polymerase (RdRp). In this review, we discuss recent breakthroughs towards the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 137 publications
(187 reference statements)
1
18
0
1
Order By: Relevance
“…Indeed, they form a separate clade for each gene. This seems to confirm that homologous recombination is an uncommon event in Morbillivirus and, in general, in non-segmented negative stranded RNA viruses 17 , 18 . However, Park et al .…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Indeed, they form a separate clade for each gene. This seems to confirm that homologous recombination is an uncommon event in Morbillivirus and, in general, in non-segmented negative stranded RNA viruses 17 , 18 . However, Park et al .…”
Section: Discussionsupporting
confidence: 71%
“…The L protein, together with the phospho- (P) protein is encapsidated into a ribonucleoprotein complex (RNP) formed by the nucleocapsid (N) protein 12 . In the morbillivirus genus, the L protein harbors all enzymatic activities necessary for RNA transcription and replication 17 . From a GenBank search for CeMV sequences at the moment of writing, the only L gene sequence publicly available can be retrieved from the reference sequence of the complete 1990 DMV genome (excluding the two Spanish sequences of our phylogenetic analysis that include only a very short region corresponding to the first 10 amino acids of the L protein).…”
Section: Discussionmentioning
confidence: 99%
“…While Ntail is structurally intrinsically disordered, areas of high sequence conservation were identified that engage in multiple protein-protein interactions [69]. A molecular recognition element (MoRE) mediates transient binding of the P-L polymerase complex [70], and the terminal residues of the Ntail were demonstrated to mediate specific contacts with the MeV M protein [71], promoting genome packaging into nascent virions.…”
Section: Interaction Of the M Protein With The Rnp Complexmentioning
confidence: 99%
“…2 × 10 5 in dieser Altersgruppe wird dennoch wegen eines möglichen Vitamin-A-Man-gels empfohlen [52]. Symptomatisch mit Vitamin A sollten vor allem pädiatrische Patienten während der asymptomatischen Expositionsphase, also vor dem klinischen Ausbruch der Infektion, behandelt werden [53].…”
Section: Therapeutische Möglichkeitenunclassified